2010
DOI: 10.1111/j.1475-4754.2009.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead Isotope Analysis of Tang Sancai Pottery Glazes From Gongyi Kiln, Henan Province and Huangbao Kiln, Shaanxi Province

Abstract: Through the use of MC–ICP–MS, this study analyses the lead isotope ratios of 19 Tang Sancai pottery glazes unearthed from the Gongyi and Huangbao kiln sites. According to their different lead isotope ratios, the two kilns can be grouped separately. The research also suggests that the Gongyi and Huangbao kilns are independent production centres of Tang Sancai in the Tang Dynasty. The data from the Huangbao kiln indicates that the lead in the glazes originates from the Northern China geochemical province, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The sample preparation procedure is described in detail elsewhere (Cui et al, 2010). The full sequence of the process is the following: 1) Small glass fragments of approximately 10 mg are chipped off using a sharp scalpel; 2) Then, the fragments are dissolved in pure nitric acid in a 50 ml glass beaker; 3) Subsequently, the clear solution is leached and diluted in a 100 ml flask using deionised water; 4) The solutions are then measured to detect the lead contents using ICP-AES; 5) According to the results representing the lead contents, the solutions are then diluted down to the tolerance limit of the instrument, which is 1 ug/l; 6) The thallium (Tl) standard SRM997 are then added in the solutions; 7) The lead isotope ratios of the samples can be measured on the MC-ICP-MS.…”
Section: Lead Isotope Analysismentioning
confidence: 99%
“…The sample preparation procedure is described in detail elsewhere (Cui et al, 2010). The full sequence of the process is the following: 1) Small glass fragments of approximately 10 mg are chipped off using a sharp scalpel; 2) Then, the fragments are dissolved in pure nitric acid in a 50 ml glass beaker; 3) Subsequently, the clear solution is leached and diluted in a 100 ml flask using deionised water; 4) The solutions are then measured to detect the lead contents using ICP-AES; 5) According to the results representing the lead contents, the solutions are then diluted down to the tolerance limit of the instrument, which is 1 ug/l; 6) The thallium (Tl) standard SRM997 are then added in the solutions; 7) The lead isotope ratios of the samples can be measured on the MC-ICP-MS.…”
Section: Lead Isotope Analysismentioning
confidence: 99%
“…Lead-based glazes usually liquefy at temperatures below 1000°C and were commonly used in China since the Han Dynasty (ca > 221) [1]. Overglaze polychrome wares coloured with copper green, iron red, antimony-iron yellow, and iron-manganese lead-glazes were produced subsequently from the 8 th century onwards [1,5,6,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The lead isotope ratios of the Tang sancai glazes analysed in this study were in accordance with those analysed by Cui et al . (), which were plotted together with the data analysed in this study, in Figures (c, d).…”
Section: Resultsmentioning
confidence: 99%
“…Cui et al . () then showed that lead isotope ratios of Tang sancai glazes could distinguish between Huangpu and Huangye kiln products.…”
Section: Introductionmentioning
confidence: 98%